Associations Between Posterior Communicating Artery Aneurysms and Morphological Characteristics of Surrounding Arteries - Hao, Weili; Hao, Hong; Ren, Chun-Feng; Wang, Xiangling; Gao, Bulang (Frontiers in Neurology, 2022)
Objectives: To explore the associations between posterior communicating artery (PComA) aneurysms and morphological characters of arteries upstream of and around PComA bifurcation site. Methods: Fifty-seven patients with PComA aneurysms and sixty-two control subjects without aneurysms were enrolled. The centerlines of internal carotid artery (ICA) and important branches were generated for measurement and analysis of morphological parameters, including carotid siphon types, diameters of two fitting circles and the angle formed by them (D1, D2, and φ), length (L) and tortuosity (TL) of ICA segment between ophthalmic artery and PComA bifurcations, bifurcation angle (θ), tortuosity (TICA and TPComA) and flow direction changes (θICA and θPComA) around the PComA bifurcation site. Results: No significant difference (P>0.05) was found in the siphon types (P=0.467) or L (P=0.114). Significant differences (P<0.05) were detected in D1 (P=0.036), TL (P＜0.001), D2 (P=0.004), φ (P=0.008), θ (P=0.001), TICA (P＜0.001), TPComA (P=0.012), θICA (P＜0.001) and θPComA (P＜0.001) between the two groups. TICA had the largest AUC (0.843) in ROC analysis in diagnosing the probability of PComA aneurysms presence and was identified as the only potent morphological parameters (OR=11.909) associated with PComA aneurysms presence. Conclusions: High tortuosity of the ICA segment around the PComA bifurcation is associated with PComA aneurysm presence.